An Appraisal of the Conduct of Nigeria's Foreign Policy from 1999 to 2003 - Olaleye, Olabisi Oluremi (2015)
This study examined how Nigeria's foreign policy was conducted in a democratic setting between 1999 and 2003. The study further assessed the effects of Nigeria's socio-political and economic situations on the country's image, and foreign policy, and how the influence and prestige of the country were restored on the international scene. This is with a view to understanding the institutions, structures and process of conducting Nigeria's foreign policy in relation to government’s concern for Africa's political stability, peace, unity and development.